Strengthening Faculty Retention and Belonging: Applying and Expanding Job Embeddedness Theory through an Onboarding Initiative in Higher Education - Tassell, Janet; Winters, Dawn; Logsdon, Jeremy; Paganelli, Andrea; Super, Daniel (Educational (Re)naissance, 2026)
This study explores the impact of a supplemental onboarding program on new faculty integration within a university’s education department, applying Job Embeddedness Theory as a guiding framework. Seven newly hired instructors participated in a year-long, intentionally designed onboarding experience aimed at fostering professional development and a sense of belonging. Using qualitative methods—including open-ended surveys and group discussions—the study examined participants’ perceptions across five emergent themes: positive overall experience, valuable presentations, skill and knowledge growth, academic community integration, and suggestions for improvement. The program’s structure supported the development of meaningful links, alignment with departmental culture (fit), and investment in experiences that increased the perceived sacrifice of leaving. Findings informed the creation of the LEF Embeddedness Model (Learning–Experiences–Feelings), which maps onboarding influences to embeddedness dimensions. Results suggest that well-designed onboarding programs can enhance faculty retention by strengthening social and professional ties, promoting cultural alignment, and deepening emotional investment. This research offers actionable insights for institutions seeking to build onboarding programs that cultivate embeddedness and reduce attrition.